Quercetin prevents liver carcinogenesis by inducing cell cycle arrest, decreasing cell proliferation and enhancing apoptosis - Casella, María Laura (2014)
Fil: Fil: Casella, María Laura. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Fisiología Experimental (IFISE-CONICET); Argentina.